2020
DOI: 10.3390/nu12030726
|View full text |Cite
|
Sign up to set email alerts
|

Antrodia cinnamomea Confers Obesity Resistance and Restores Intestinal Barrier Integrity in Leptin-deficient Obese Mice

Abstract: Obesity is associated with metabolic disorders. Thus, obesity prevention and treatment are essential for health. Antrodia cinnamomea (AC) is a multifunctional medicinal fungus used for the treatment of various diseases and for preventing diet-induced obesity. Leptin deficiency causes over-eating and spontaneous obesity. The concomitant metabolic symptoms are more severe than diet-induced obesity. Here, we used leptin-deficient (ob/ob) mice as an animal model for over-feeding to study the effect of AC on obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…All these phenotypes were resulted from normal diet chow, similar to the human population with the same genotype 19,[21][22][23] . The model is different from obesity linked to diabetes models, such as over-expressing fat mass and obesity-associated (FTO) mice 44 , mice with genetic deletions of melanocortin 4 receptor(MC4R) 45 leptin-de cient mice 46 and zebra sh obesity models 47 , in which the obesity phenotype was primarily caused by increased appetite and food intake and decreased physical activity 48 . The CREBRF p.Arg457Gln pigs could store more fat without overeating.…”
Section: Discussionmentioning
confidence: 99%
“…All these phenotypes were resulted from normal diet chow, similar to the human population with the same genotype 19,[21][22][23] . The model is different from obesity linked to diabetes models, such as over-expressing fat mass and obesity-associated (FTO) mice 44 , mice with genetic deletions of melanocortin 4 receptor(MC4R) 45 leptin-de cient mice 46 and zebra sh obesity models 47 , in which the obesity phenotype was primarily caused by increased appetite and food intake and decreased physical activity 48 . The CREBRF p.Arg457Gln pigs could store more fat without overeating.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in the leptin-induced Caco-2 cells model found that AC had a positive effect on intestinal microflora by repairing intestinal-barrier damage and enhancing the integrity of the intestinal barrier ( Tsai et al, 2020 ). Another study in high-fat diet (HFD)-fed mice demonstrated that AC showed protective effects, maintained the intestinal barrier integrity, reduced the Firmicutes/Bacteroidetes ratio and increased Akkermansia muciniphila level ( Chang et al, 2018 ).…”
Section: Potential With the Gut-microbiome-brain Axis Of Acmentioning
confidence: 99%